Analysis of Training Evaluation Process Using KIRKPATRICK'S Traininng Evaluation Model at PT. Bank Tabungan Negara (Persero) Tbk. - Ikramina, Fildzah; Gustomo, Aurik (Journal of Business and Management, 2014)
Abstract- The main topic of this research is finding problems and gap using training evaluation model in PT Bank Tabungan Negara (Persero) Tbk, then coming up with a way to reduce it. In order to know whether the training is successful or not, it is needed to evaluate the training, one of the methods is Kirkpatrick’s the four levels training evaluation model. In this research, the training evaluation program in BTN is analyzed by interviewing the learning division manager and also by comparing the existing training evaluation design used by BTN with the theory that is stated by Kirkpatrick. The training evaluation program is analyzed to see the behavioral change in behavior level of evaluation. This research will show the result of the listing problems that happened in behavior level of evaluation, and also will state the gap that occurred between the theory and the implementation in BTN current training evaluation design. Furthermore, the list of possible recommendations such as coaching and making control group which also will be stated as the end result to be proposed to BTN in order to improve future training evaluation design. Keywords: training, training evaluation program, BTN, comparison, Kirkpatrick, gap, coachingCategory: human capital management